Lower urinary tract symptoms in pre-menopausal women and its association with sexual dysfunction - Mishra, Gourav Kumar; Mishra, Urvashi; Hasan, Arshad; Ahmad, Ahsan; Jabin, Nusrat; Chandra, Vipin Kumar (Asian Journal of Medical Sciences, 2021)
Background: Sexual dysfunction (SD) is one of the common problems observed by premenopausal women and it frequently exists along with other associated lower urinary tract symptoms (LUTS). Aims and Objective: The present study was planned to evaluate the correlation between SD in pre-menopausal women with LUTS. Materials and Methods: This was a prospective observational study conducted between March 2018 to February 2019. All sexually active premenopausal women, who presented with complains of LUTS were enrolled in this study. All included patients were given two types of questionnaires (Bristol female lower urinary tract symptom [BFLUTS] and pelvic organ prolapse-urinary incontinence sexual function [PISQ-12]). These were for the assessment of LUTS and sexual function. Assessment of association between presence of LUTS and sexual dysfunction was done. Results: A total of 105 women were enrolled in the study. Their mean age was 43.70 years and BMI was 29.49. The total mean BFLUTS score recorded was 28.12. Their sub-dimension scores recorded for the filling, voiding, incontinence symptoms, sexual function and quality of life were 8.21, 34.32, 12.21, 4.49, and 10.65, respectively. Total mean score of PISQ-12 was 23.72 in all women and the mean values for the sub-dimension scores were 5.21 for the behavioural-emotive state, 11.78 for the physical state, and 6.2 for the partner-related state. There was Negative association observed between the total of PISQ-12 scores and total and sub-dimension of the BFLUTS scores (p<0.01). Conclusion: This study observes the presence of LUTS in women with sexual dysfunction. LUTS directly or indirectly increase the sexual problems in premenopausal women. These results highlight the clinical importance of evaluating LUTS in premenopausal women with sexual dysfunction.